Optimalisasi Pangkalan Data BPBL Provinsi Papua Tengah Berbasis Web Menggunakan Metode Waterfall - Arief Rahman Hakim; Anjarwati Anjarwati (STMIK Pesat Nabire, 2025)
This research focuses on the optimization of BPBL data management processes through a custom application. The study identifies the challenges faced in manual data entry and verification, which can lead to inefficiencies and errors. The objective is to develop an application that allows for a one-click verification of application statuses, improving efficiency and accuracy. The findings suggest that such an application could significantly reduce processing time and enhance data integrity.